The Antimicrobial Peptide Human β-Defensin-3 Accelerates Wound Healing by Promoting Angiogenesis, Cell Migration, and Proliferation Through the FGFR/JAK2/STAT3 Signaling Pathway - Takahashi, Miho; Umehara, Yoshie; Yue, Hainan; Trujillo-Paez, Juan Valentin; Peng, Ge; Nguyen, Hai Le Thanh; Ikutama, Risa; Okumura, Ko; Ogawa, Hideoki; Ikeda, Shigaku; Niyonsaba, François (Frontiers in Immunology, 2021)
In addition to its antimicrobial activity, the skin-derived antimicrobial peptide human -defensin-3 (hBD-3) promotes keratinocyte proliferation and migration to initiate the wound healing process; however, its effects on fibroblasts, which are the major cell type responsible for wound healing, remain unclear. We investigated the role of hBD-3 in cell migration, proliferation and production of angiogenic growth factors in human fibroblasts and evaluated the in vivo effect of hBD-3 on promoting wound healing and angiogenesis. Following hBD-3 treatment, the mouse wounds healed faster and showed accumulation of neutrophils and macrophages in the early phase of wound healing and reduction of these phagocytes 4 days later. hBD-3-treated wounds also displayed an increased number of fibroblasts and newly formed vessels compared to those of the control mice. Furthermore, the expression of various angiogenic growth factors was increased in the hBD-3-treated wounds. Additionally, in vitro studies demonstrated that hBD-3 enhanced the secretion of angiogenic growth factors such as fibroblast growth factor, platelet-derived growth factor and vascular endothelial growth factor and induced the migration and proliferation of human fibroblasts. The hBD-3-mediated activation of fibroblasts involves the fibroblast growth factor receptor 1 (FGFR1)/Janus kinase 2 (JAK2)/signal transducer and activator of transcription 3 (STAT3) pathways, as evidenced by the inhibitory effects of pathway-specific inhibitors. We indeed confirmed that hBD-3 enhanced the phosphorylation of FGFR1, JAK2 and STAT3. Collectively, the current study provides novel evidence that hBD-3 might be a potential candidate for the treatment of wounds through its ability to promote wound healing, angiogenesis and fibroblast activation.